Technology Of Professional-Personal Training Development Of Academic Lyceum Students Of The Ministry Of Interior Affairs - Ismailov Alisher Ulugbekovich (Zien Journals, 2024)
This article presents opinions on the technology of development of professional and personal training of academic lyceum students of the Ministry of Internal Affairs.
Keywords: Pedagogical; technology; interactive method; professional training